Lack of association between HLA-E polymorphisms and transitional cell carcinoma of the bladder - Veiga-Castelli, L. C. (2013)
Divisão de Imunologia Clínica Departamento de Clínica Médica, Faculdade de Medicina de Ribeirão Preto (FMRP) Universidade de São Paulo (USP), Ribeirão Preto